2021
DOI: 10.1074/jbc.ra120.016012
|View full text |Cite
|
Sign up to set email alerts
|

The muscle-relaxing C-terminal peptide from troponin I populates a nascent helix, facilitating binding to tropomyosin with a potent therapeutic effect

Abstract: The conserved C-terminal end segment of troponin I (TnI) plays a critical role in regulating muscle relaxation. This function is retained in the isolated C-terminal 27 amino acid peptide (residues 184–210) of human cardiac TnI (HcTnI-C27): When added to skinned muscle fibers, HcTnI-C27 reduces the Ca 2+ -sensitivity of activated myofibrils and facilitates relaxation without decreasing the maximum force production. However, the underlying mechanism of HcTnI-C27 function is unknown. We stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 76 publications
(123 reference statements)
0
6
0
Order By: Relevance
“…We previously demonstrated that the C-terminal end 27 AA (C27) segment of TnI recognized by mAb TnI-1 binds Tm (Zhang, Akhter et al 2011). The cTnI-C27 epitope structure was preserved in both isolated C27 peptide of TnI and in intact cTnI as detectable by mAb TnI-1 (Wong, Feng et al 2019) and functions as an activated state myofilament Ca 2+ desensitizer (Wong, Feng et al 2019, Hornos, Feng et al 2021). Therefore, we further tested whether the TnI-1 epitope structure resumed in the C-terminal end segment of cTnT also binds Tm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously demonstrated that the C-terminal end 27 AA (C27) segment of TnI recognized by mAb TnI-1 binds Tm (Zhang, Akhter et al 2011). The cTnI-C27 epitope structure was preserved in both isolated C27 peptide of TnI and in intact cTnI as detectable by mAb TnI-1 (Wong, Feng et al 2019) and functions as an activated state myofilament Ca 2+ desensitizer (Wong, Feng et al 2019, Hornos, Feng et al 2021). Therefore, we further tested whether the TnI-1 epitope structure resumed in the C-terminal end segment of cTnT also binds Tm.…”
Section: Resultsmentioning
confidence: 99%
“…The mAb TnI-1 recognized C-terminal end segment of TnI is a Ca 2+ -regulated allosteric Tm-binding structure in the troponin complex (Zhang, Akhter et al 2011). The C-terminal end 27 amino acids segment of cardiac TnI (cTnI-C27) binds Tm in the form of free peptide with functional effect on reducing the Ca 2+ sensitivity of activated cardiac muscle strips (Wong, Feng et al 2019, Hornos, Feng et al 2021.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in aging-induced and cardiac disorder-induced diastolic abnormalities indicate the potential for therapeutic applications of our findings. The effects of cTnI-ND provide information for targeting the sarcomere with small molecules or peptides such as that derived the COOH-terminus of cTnI [34]. The success in the use of small molecules for inhibition of the hypercontractility in the clinical course of advanced HCM [35] indicates the importance of detection of new targets to address the diverse responses to triggering mutations in HCM [36].…”
Section: Discussionmentioning
confidence: 99%
“…Thermal denaturation midpoints of the isolated importin species or of the corresponding complexes were determined as described elsewhere [ 44 ]. Thermal denaturations were used because, if there is binding, the thermal denaturation midpoint of the complex with NLS-Myc should increase when compared with that of either isolated Impα3 or ΔImpα3 [ 48 ].…”
Section: Methodsmentioning
confidence: 99%